ANALISIS SOAL PENILAIAN TENGAH SEMESTER IPA KELAS IX DENGAN RASCH MODEL - Nena Setia Nurani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This research aims to provide information regarding the quality of the questions given in the mid-semester assessment. In this research, quantitative methods and Rasch modeling were used to determine the level of difficulty of the questions and the suitability of the questions. From the measurement item analysis that has been carried out, there are 5 questions in the difficult category, 10 questions in the medium category and 5 questions in the easy category. There are 5 questions that are not appropriate, namely questions number 3, 6, 10, 18, and 20.